Estimasi Persamaan Sistem Non Linear Seemingly Unrelated Regression pada Model Perdagangan lnternasional - Ekananda, Mahyus (UI Scholars Hub, 2004)
The purpose cf this paper is to explain the algorithm solution for system equation which has non linier form in its parameter, especially in system equation of seemingly unrelated regression. For example, the economic model which is used in this paper is taken from dissertation of Ekananda (2003) with its topic of the uncertainty of exchange rates volatility on manufacture commodity export in Indonesia. Particularly, this paper will discuss the model formation by inserting poisons probability function, which cause the non linier form. For the next application, this method can be used for all non linier form especially the non linier form on its parameter. This paper will discuss the utilization of trade standard equation which is developed become non linier system equation of trade by inserting the element of poisons probability, the dynamics of equation and the simultaneous equation.